Penerapan Teknik Penyuntingan Kontinuitas dalam Video Dokumenter “Batas Tanpa Batas” - Iwan Koswara; Jimi Narotama Mahameruaji; Hardifa Reinka Khairani (IAI Nasional Laa Roiba Bogor, 2024)
Inclusive and equitable education for children with special needs (ABK) in Indonesia still faces various significant challenges. This writing analyzes the application of continuity editing techniques in the documentary video